Human Cytomegalovirus and Autoimmune Disease. (29th April 2014) - Halenius, Anne; Hengel, Hartmut
Abstract : Human cytomegalovirus (HCMV) represents a prototypic pathogenic member of the β -subgroup of the herpesvirus family. A range of HCMV features like its lytic replication in multiple tissues, the lifelong persistence through periods of latency and intermitting reactivation, the extraordinary large proteome, and extensive manipulation of adaptive and innate immunity make HCMV a high profile candidate for involvement in autoimmune disorders. We surveyed the available literature for reports on HCMV association with onset or exacerbation of autoimmune disease. A causative linkage between HCMV and systemic lupus erythematosus (SLE), systemic sclerosis (SSc), diabetes mellitus type 1, and rheumatoid arthritis (RA) is suggested by the literature. However, a clear association of HCMV seroprevalence and disease could not be established, leaving the question open whether HCMV could play a coresponsible role for onset of disease. For convincing conclusions population-based prospective studies must be performed in the future. Specific immunopathogenic mechanisms by which HCMV could contribute to the course of autoimmune disease have been suggested, for example, molecular mimicry by UL94 in SSc and UL83/pp65 in SLE patients, as well as aggravation of joint inflammation by induction and expansion of CD4+/CD28− T-cells in RA patients. Further studies are needed to validate these findings and to lay the grounds for targeted therapeutic intervention.